Improving the Ability of the Physical Education Teachers from the Four th Elementary School Region III Ko to Tangah District of Padang in Understanding - Maidarman Maidarman (Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Uiveristas Negeri Padang Jl. Prof. Hamka, Air Tawar Padang 25131 Telp. 0751-7059901, 2019)
Abstract Various problems faced by Sports and Health Physical Education Subjects (PJOK) in SDN Cluster IV Region III Koto Tangah Padang District in understanding and implementing the 2013 Curriculum. These problems need to be resolved so that the quality of learning can be improved. Priority problems to two aspects, namely PJOK teachers do not understand and apply: (1) Authentic assessment in the form of a grid and (2) Understanding, making and applying the concept rubric of performance assessment, product assessment, attitude assessment. Problem solving is done by: making models, writing teaching materials, presenting material, training, and applying. After presenting the material, the level of mastery of Mitra SDN teachers on the training material increased. (1) 77.21% authentic assessments in the form of lattices have been mastered by Mitra SDN teachers, and (2) 76.47% have understood, made and applied the rubric of performance assessment, product assessment, attitude assessment.